From Medicine to Poison: Discursive Shifts in Nineteenth-Century Opium Advertisements in Small Town Newsprint in the United States - Burns, Andrew (Stan Rzeczy, 2021)
Before sweeping legal changes in the United States in the early twentieth century, opium and other psychoactive substances were publicly available and advertised in various media. This article analyses rhetoric relating to opium and opiate products in advertisements through the dynamic consideration of available newsprint advertising and adjacent news stories from a single community and geographic area, Sandusky, Ohio, between 1825 and 1909. The results illustrate non-linear trajectories for opium-based patent medicines from banal to heroic, to useful negation, to poison. The findings include deceptive ads fashioned to look like tragic news stories, non-opiate patent medicines, and local sanitaria promoting liquor and opium cures. This research illustrates the systematic use of print advertising content for micro-historical social analysis within a local context, providing depth to an otherwise forgotten social phenomenon.